Integrative Genomic-Epigenomic Analysis of Clozapine-Treated Patients with Refractory Psychosis - Yerye Gibrán Mayén-Lobo; José Jaime Martínez-Magaña; Blanca Estela Pérez-Aldana; Alberto Ortega-Vázquez; Alma Delia Genis-Mendoza; David José Dávila-Ortiz de Montellano; Ernesto Soto-Reyes; Humberto Nicolini; Marisol López-López; Nancy Monroy-Jaramillo (MDPI AG, 2021)
Clozapine (CLZ) is the only antipsychotic drug that has been proven to be effective in patients with refractory psychosis, but it has also been proposed as an effective mood stabilizer; however, the complex mechanisms of action of CLZ are not yet fully known. To find predictors of CLZ-associated phenotypes (i.e., the metabolic ratio, dosage, and response), we explore the genomic and epigenomic characteristics of 44 patients with refractory psychosis who receive CLZ treatment based on the integration of polygenic risk score (PRS) analyses in simultaneous methylome profiles. Surprisingly, the PRS for bipolar disorder (BD-PRS) was associated with the CLZ metabolic ratio (pseudo-R2 = 0.2080, adjusted p-value = 0.0189). To better explain our findings in a biological context, we assess the protein-protein interactions between gene products with high impact variants in the top enriched pathways and those exhibiting differentially methylated sites. The GABAergic synapse pathway was found to be enriched in BD-PRS and was associated with the CLZ metabolic ratio. Such interplay supports the use of CLZ as a mood stabilizer and not just as an antipsychotic. Future studies with larger sample sizes should be pursued to confirm the findings of this study.